A Cognitive Stylistic Analysis of Retroactive Jealousy in Niki’s ‘Did You Like Her in The Morning? - Sarah Safika Sitorus; Ibnati Faiza Hamdi; Rahmadsyah Rangkuti (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
Retroactive jealousy refers to feelings of insecurity and concern about a partner’s previous romantic relationships. This study aims to examine how retroactive jealousy is represented in NIKI’s song Did You Like Her in the Morning? through interpersonal meaning, framing, and metaphor. Using a cognitive stylistic approach, the study combines Systemic Functional Linguistics (SFL), Frame Analysis, and Conceptual Metaphor Theory. The data consist of the song lyrics obtained from Spotify and were analyzed qualitatively through data collection, identification of linguistic features, and interpretation. The findings reveal that the frequent use of interrogative sentences constructs interpersonal meaning by positioning the narrator as uncertain and emotionally vulnerable toward the partner’s past. The lyrics further employ framing strategies that present the former partner as a significant figure in the narrator’s imagination. In addition, metaphors such as weightless and heavy transform abstract emotions into concrete physical experiences, highlighting feelings of jealousy, comparison, and insecurity. These findings demonstrate how linguistic choices contribute to the construction of retroactive jealousy and show how contemporary song lyrics communicate complex emotional experiences.